Prehospital Nitroglycerin in Tachycardic Chest Pain Patients: A Risk for Hypotension or Not?. (2nd January 2017) - Proulx, Marie-Hélène; de Montigny, Luc; Ross, Dave; Vacon, Charlene; Juste, Louis Enock; Segal, Eli
Abstract: Background: The American Heart Association guidelines (AHA) guidelines list tachycardia as a contraindication for the administration of nitroglycerin (NTG), despite limited evidence of adverse events. We sought to determine whether NTG administered for chest pain was a predictor of hypotension (systolic blood pressure <90 mmHg) in patients with tachycardia, compared to patients without tachycardia (50≥ heart rate ≤100).Methods: We performed a retrospective cohort study using patient care reports completed by basic life support (BLS) providers in a large urban Canadian EMS system for the period 2010–2012. We used logistic regression to test the association between post-NTG hypotension and tachycardia, independent of pre-NTG blood pressure, age, sex, and comorbidities. Using identical models, we tested four secondary outcomes (drop in blood pressure, reduced consciousness, bradycardia, and cardiac arrest).Results : The cohort included 10, 308 patients who were administered NTG by BLS in the prehospital setting; 2, 057 (20%) of patients were tachycardic before NTG administration. Hypotension occurred in 320 of all patients (3.1%): 239 without tachycardia (2.9%) and 81 with tachycardia (3.9%). Compared to non-tachycardic patients, tachycardic patients showed increased adjusted odds of hypotension (AOR: 1.60; 95% CI: 1.23–2.08) or of a drop in blood pressure of 30mm Hg or greater (AOR: 1.11; CI: 1.00–1.24). Tachycardia was associated with decreased odds of bradycardia (OR: 0.33; CI: 0.17–0.64). We did not find a significant association between tachycardia and either post-NTG reduced level of consciousness or cardiac arrest. We did find a strong, significant association between pre-NTG blood pressure and post-NTG hypotension (AOR for units of 10mmHg: 0.64; CI: 0.61–0.69).Conclusion: Hypotension following prehospital administration of NTG was infrequent in patients with chest pain. However, while the absolute risk of NTG-induced hypotension was low, patients with pre-NTG tachycardia had a significant increase in the relative risk of hypotension. In addition, hypotension occurred most frequently in patients presenting with a lower pre-NTG blood pressure, which may prove to be a more discriminating basis for future guidelines. EMS medical directors should review BLS chest pain protocols to weigh the benefits of NTG administration against its risks.